2007
DOI: 10.1111/j.1600-079x.2007.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin antagonizes apoptosis via receptor interaction in U937 monocytic cells

Abstract: Among the non-neurological functions of melatonin, much attention is being directed to the ability of melatonin to modulate the immune system, whose cells possess melatonin-specific receptors and biosynthetic enzymes. Melatonin controls cell behaviour by eliciting specific signal transduction actions after its interaction with plasma membrane receptors (MT(1), MT(2)); additionally, melatonin potently neutralizes free radicals. Melatonin regulates immune cell loss by antagonizing apoptosis. A major unsolved que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 50 publications
5
53
0
1
Order By: Relevance
“…Studies in peripheral blood have suggested that melatonin inhibits apoptotic processes via its antioxidant properties [106], which is in line with many evidences showing that in some instances the apoptotic process occurs via oxidative signaling [107]. Alternative mechanisms have been proposed; in U937 monocytes, melatonin reduces apoptosis via intracellular signal transduction stimulated by interaction with MT1/MT2 plasma membrane receptors [23]. However, the majority of reports indicate that the anti-apoptotic of melatonin occurs by acting on the abundance of the two main members of the Bcl-2 family, namely the pro-apoptotic Bax and the anti-apoptotic Bcl-2 proteins [108].…”
Section: Page 9 Of 29supporting
confidence: 52%
See 3 more Smart Citations
“…Studies in peripheral blood have suggested that melatonin inhibits apoptotic processes via its antioxidant properties [106], which is in line with many evidences showing that in some instances the apoptotic process occurs via oxidative signaling [107]. Alternative mechanisms have been proposed; in U937 monocytes, melatonin reduces apoptosis via intracellular signal transduction stimulated by interaction with MT1/MT2 plasma membrane receptors [23]. However, the majority of reports indicate that the anti-apoptotic of melatonin occurs by acting on the abundance of the two main members of the Bcl-2 family, namely the pro-apoptotic Bax and the anti-apoptotic Bcl-2 proteins [108].…”
Section: Page 9 Of 29supporting
confidence: 52%
“…Indeed, melatonin inhibits apoptosis of precursor B cells in mouse bone marrow [105]. Moreover, an anti-apoptotic effect on different leukocytes was also demonstrated [23,102].…”
Section: Page 9 Of 29mentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, suitable chelators may prevent ADR-mediated cytotoxicity and potentiate its antitumor activity. MLT binds iron (Limson et al, 1998;Maharaj et al, 2003), exerts remarkable oncostatic and antiproliferative effects on different kinds of tumors (El-Missiry and Abd El-Aziz, 2000;Cos and SanchezBarcelo, 1995) and antagonizes apoptosis (Radogna et al, 2007). Thus, MLT might have dual actions; control ADR-mediated disturbance of iron homeostasis and decreasing oncogenesis.…”
Section: Effect Of Melatonin On Adr Toxicitymentioning
confidence: 97%